A comparative study of bioenergetic metabolism on mammary epithelial cells from humans and Göttingen Minipigs - Algieri, Cristina; Bernardini, Chiara; La Mantia, Debora; Trombetti, Fabiana; Forni, Monica; Nesci, Salvatore (Biochimica et biophysica acta. General subjects, 2024)
Mammary epithelial cells (MECs) of humans (h) and Göttingen Minipigs (mp) were analyzed to compare their ability to perform ATP production by oxidative phosphorylation and glycolysis. The ATP production under basal and stressor situations highlights the same metabolic potential of both primary cell lines. However, quantitively the ATP production rate of hMECs was higher than mpMECs. Conversely, oxidative cell respiration in mpMECs exploits a maximum respiratory capacity to support pathophysiological circumstances or stress conditions that could require an excessive effort of cell metabolism. Since mpMECs primarily utilize an oxidative metabolism similar to hMECs, the metabolic characterization conducted allows us to confirm that mpMECs represent a potential alternative cellular model in the translational medicine approach.